Producer,s Factors and Mechanisms of Manna in Iran - S Takavar; M Mohamadi (Institue of Medicinal Plants, ACECR, 2008)
Manna is a peculiar odour and a sweetish taste of the food miraculously produced in plains and forests. Ecological variation and rich Fauna and flora in Iran is caused to form the kinds of unique manna with special formula and with peculiar production mechanisms. From olden times, kinds of Manna were used in traditional medicine by sages, such as Ibn Sina. Astragal Manna, Camel,s thorn Manna, Tamarisk Manna, Oak Manna, Trehala Manna, Cotoneaster Manna, Willow Manna and Anzaroot Manna are important kinds of manna in Iran. Scientific knowledge about the kinds of manna productive species and mechanisms is necessary for Constant revenue of these unique value sources particularly for them that their origin is restricted to areas of Iran. So in the present article, we review producer,s factors and mechanisms of manna in Iran.